HOME IN THE POETRY OF SAUDI ARABIA POETS: KHALID AL-FAISAL AN EXAMPLE OF A DISTINGUISHED ARAB (2) - Dahami, Yahya Saleh Hasan (UIN Sumatera Utara, 2023)
It is well known that when a philosopher articulates his or her love for and affiliation with the homeland, he or she may represent the great homeland through a limited part of this homeland. It is worth noting that Makkah Al-Mukarramah is simply a small, light representation of the great homeland, which embraces Makkah Al-Mukarramah like the heart of the body. Consequently, through the striking poem